Pengaruh Laba Akuntansi, Arus Kas Operasi Terhadap Return Saham Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Yunita Althin Natanael (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to determine how the influence of cash flow, accounting profit, profitability, and inflation on stock returns in food and beverage companies listed on the IDX for 2017-2019 period. This study uses secondary data obtained through company financial reports. The sample selection method in this study using purposive sampling, the sample in this study were 13 companies. The data analysis used descriptive statistical test, classic assumption test, and hypothesis test using multiple linear regression method. The results of multiple linear regression analysis show that partially it shows the accounting profit and operating cash flow variables do not have a significant effect on stock returns. And simultaneously, it shows that accounting profit and operating cash flow variables do not have a significant effec